Analisis Peraturan Menteri Ketenagakerjaan Nomer 18 Tahun 2018 Tentang Jaminan Sosial Pekerja Migran Indonesia - Mohammad Andik Juliantoro; Santi Wijaya; Dian suluh K D (Jurnal Ilmu Politik dan Pemerintahan, 2020)
The protection of Indonesian migrant workers is still very sad, as quoted from the Migrant Care record, in the range of 278 Indonesian migrant workers are threatened with the death penalty and 59 of them have been sentenced. This is very interesting with the issuance of the Minister of Manpower Regulation 18 of 2018 concerning the social security of Indonesian Migrant workers the question arises as to how the implementation of this policy? social security is included in worker safety. This study aims to analyze the analysis of the Indonesian Minister of Manpower's regulation which issued Number 18 of 2018 policy on the social security of Indonesian migrant workers. The research method uses qualitative research with a focus of research on how the implementation of Minister of Manpower regulation number 18 of 2018 concerning social security of Indonesian migrant workers. The data collection is done by means of a literature study using internet access methods. The data collected is then analyzed using the Narrative Analysis method.